Modification of Cellulose for Preparing Hydrogels and Removing Metals in Contaminated Water - Rodrigues, Jéssica S. [UNESP]; Senna, André M.; Botaro, Vagner R. (Wiley, 2025)
This chapter focuses on the modification of cellulose to prepare hydrogels and their application in removing metals from contaminated water. Hydrogels are a class of polymers known for their ability to absorb large amounts of water and physiological fluids without dissolving. The chapter details the challenges of preparing hydrogels from cellulose due to its insolubility in conventional organic solvents, and how modifying the cellulose structure, specifically by substituting hydroxyl groups with chemical groups that have weaker intermolecular forces, allows it to dissolve in organic solvents. This modification opens the possibility to synthesize cellulose-derived hydrogels in homogeneous media, thus facilitating their application in various fields. The chapter also explores several methods for cellulose dissolution and hydrogel formation, such as using ionic liquids, alkali/urea systems, and bacterial cellulose. Additionally, the potential of cellulose derivatives like cellulose acetate in the production of hydrogels is discussed, emphasizing their importance in various industrial and biomedical applications, including water purification and metal removal from contaminated water.
Keywords: bacterial cellulose; cellulose acetate; cellulose derivatives; Cellulose modification; contaminated water; environmental sustainability; hydrogels; ionic liquids; metal removal; water purification